Boron-doped diamond electrodes: Growth, surface characterisation and sono-electrochemical applications - Goeting, C; Marken, F; Gutierrez-Sosa, A; Compton, R; Foord, J (1999)
Mechanically stable and highly conductive boron-doped diamond electrodes suitable for work in corrosive and heavy duty environments were produced by depositing adherent boron-doped diamond films on tungsten substrates using a hot filament reactor. The diamond film electrodes were investigated by Raman spectroscopy, scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS) and used in both conventional and sono-electrochemical experiments. In order to obtain robust and highly adherent diamond films, controlling the boron doping is of utmost importance. A controlled shutdown procedure was found to improve bonding between tungsten substrate and diamond and minimises stress in diamond films. Applying a positive bias to the sample during growth enhances nucleation and hence also improves adhesion. The growth rate, quality and efficiency of the diamond CVD procedure can be enhanced using an upstream reactor configuration. The diamond electrodes were stable under power ultrasound conditions with mechanical strain induced by pressure waves of approximately 10 bar amplitude and interfacial cavitation. In addition, the diamond films remained adherent to the tungsten surface even after annealing at temperatures up to ∼1200°C in vacuum and temperatures of ∼700°C in air. The electrochemical properties of the diamond electrodes were investigated with and without power ultrasound using electrochemical processes in aqueous solutions, with redox systems such as the one-electron reduction of Ru(NH3)63+, the one-electron oxidation of FeCN64-, the more complex O2 reduction process and Ag+ deposition and "stripping." The diamond electrodes were surface-modified by electrochemical treatment and by electron beam irradiation. XPS studies show that the diamond electrode surfaces are considerably modified by electrochemical treatments.